Surprisingly high activity for oxygen reduction reaction of selected oxides lacking long oxygen-ion diffusion paths at intermediate temperatures: A case study of cobalt-free BaFeO3-δ - Dong, F.; Chen, Y.; Chen, D.; Shao, Zongping (American Chemical Society, 2014)
The widespread application of solid oxide fuel cell technology requires the development of innovative electrodes with high activity for oxygen reduction reaction (ORR) at intermediate temperatures. Here, we demonstrate that a cobalt-free parent oxide BaFeO 3 δ (BF), which lacks long-range oxygen-ion diffusion paths, has surprisingly high electrocatalytic activity for ORR. Both in situ high-temperature X-ray diffraction analysis on room-temperature powder and transmission electron microscopy on quenched powder are applied to investigate the crystal structure of BF. Despite the lack of long oxygen-ion diffusion paths, the easy redox of iron cations as demonstrated by thermal gravimetric analysis (TGA) and oxygen temperature-programmed desorption and the high oxygen vacancy concentration as supported by iodometric titration and TGA bene fi t the reduction of oxygen to oxygen ions. Moreover, the electrical conductivity relaxation technique in conjunction with a transient thermogravimetric study reveals very high surface exchange kinetics of BF oxide. At 700 ° C, the area specific resistance of BF cathode, as expressed by a symmetrical cell con figuration, is only ~0.021 Ω cm 2 , and the derived single fuel cell achieves high power output with a peak power density of 870 mW cm − 2 . It suggests that an undoped BF parent oxide can be used as a high-efficiency catalyst for ORR.